Anatomie Et Histologie De L’hepatopancreas Chez Le Male Du Poisson Brachydeuterus Auritus (Haemulidae, Valenciennes, 1831) En Cote D’ivoire - Komenan Daouda Kouassi; Marie-Anne D’Almeida; Jean Jacques Miessan; Silvain Yao; Valentin N’Douba; Goueh Gnahoue (European Scientific Journal, ESJ, 2017)
Brachydeuterus auritus is a fish species with a high level of exploitation potential in Côte d'ivoire. The following study is based upon a maturity ladder and the discrimination of the hepatopancreas. The methodological approach consisted of a macroscopic description of the hepatopancreas according to the five stages of sexual maturity. The microscopic study consisted of fixing the hepatopancreas, dehydrating, impregnating, including it, making cuts that are colored for observation. At the macroscopic level, the hepatopancreas is made of two unequal lobes. The organ has a colouring as well as a vascularization varying in terms of the species development stages. At the microscopic level among the males, the hepatopancreas is a mixed organ made of the liver and the pancreas. The hepatopancreatic parenchyma is an homogeneous tissue made of hematocytes which are polygonal cells. In addition, we can find hematopoietic tissues in the parenchyma and melanomacrophages centers located near the blood vessels and the biliary tracts. The melanomacrophages centers are formed with cells accumulating pigment cells. Inside the organ, the pancreas is discriminated centripally and constituted of exocrine cells and Langerhans islets. The physiology of the two entities (liver and pancreas) will establish the organ's physiology. Hepatopancreas is involved in reproduction, digestion and defence. It exists as an organ that controls many functions and plays an important part in the physiology of fish in anabolism and catabolism.